Bibliographic Study Of Pawon Man Forensic Odontology Research At Universitas Padjadjaran, Indonesia - Wulandari, Felia Resha; Yondri, Lutfi; Suhardjo; Mardhian, Deby Fajar; Susilawati, Sri; Oscandar, Fahmi (Badan Riset dan Inovasi Nasional (BRIN), 2025)
Discovery of Pawon Man provide valuable insights into the region's history. Despite various studies conducted, there is a notable lack of comprehensive identification and systematic review of Pawon Man's teeth. This study aims to map the development of research on Pawon Man in the field of forensic odontology, which contributes to the understanding of human history in West Java. The method used is descriptive analysis, examining technology applied in research by analysing relevant references from 2012 to 2024. 3D Cone Beam Computed Tomography (CBCT) was the method used in 16 studies due to its non-destructive and high accuracy. Scanning Electron Microscope (SEM) provided in-depth insights into dental calculus, revealing information about ancient health and dietary practices. In a review of 33 articles, the study also highlighted age estimation as a crucial aspect of biological profiling. Despite extensive research, there are still variables that require further investigation, including accuracy in age estimation and contributing factors to the absence of dental caries. Interdisciplinary collaboration is essential to address these issues and enrich the understanding of Pawon Man. Future studies should prioritise interdisciplinary approaches and the use of advanced technology.